Modernizing Maritimes Motorsport: Creating Atlantic Motorsport Park, 1959-1979 - Charters, David A. (Acadiensis, 2025)
This article uses the creation of Atlantic Motorsport Park (AMP), the only purpose-built road racing circuit in Atlantic Canada, as a lens to explain the wider efforts to modernize sports car competition in the region. Those efforts paralleled the contemporaneous regional political attempts to embrace industrial modernity that culminated in the illfated Bricklin sports car. Just as major changes in the auto industry helped to sink the Bricklin project, AMP eventually was overtaken by modernizing changes in Canadian motorsport, specifically commercialized professionalism. The voluntary efforts that built the track limited its ability to host the “big-league” races it was designed to attract. Ironically, while professional racing shifted to city-based circuits, the modest scale and the volunteer character of AMP ensured its survival as a club-operated venue for amateur motorsport.